Prevalence of Polyclonal mefA-Containing Isolates among Erythromycin-Resistant Group A Streptococci in Southern Taiwan - Yan, Jing-Jou (American Society for Microbiology, 2000)
A total of 204 nonrepetitive isolates of group A streptococci (GAS), including 107 randomly collected between 1992 and 1995 and 66 and 31 consecutively collected in 1997 and 1998, respectively, from a university hospital in southern Taiwan were examined to determine the prevalence and mechanisms of erythromycin resistance among these isolates. Resistance to erythromycin was detected in 129 isolates (63.2%) by the agar dilution test. Of these, 42 isolates (32.6%) were assigned to the constitutive macrolide, lincosamide, and streptogramin B resistance (cMLS) phenotype, and all carried the ermB gene; 4 (3.1%) were assigned to the inducible MLS resistance (iMLS) phenotype, and all harbored the ermTR gene; and 83 (64.3%) were erythromycin resistant but susceptible to clindamycin (M phenotype), and all possessed the mefA gene. Distributed by years, the rates of erythromycin resistance and different phenotypes were 61.7% (53.0% cMLS, 6.1% iMLS, and 40.9% M phenotype) between 1992 and 1995, 62.1% (12.2% cMLS and 87.8% M phenotype) in 1997, and 71.0% (9.1% cMLS and 90.9% M phenotype) in 1998. Pulsed-field gel electrophoresis showed that all but 2 cMLS isolates were clonal in origin, and 17 clones were detected among the M-phenotype isolates. These results indicate that the high incidence and increasing rate of erythromycin-resistant GAS in southern Taiwan are due to the prevalence of multiple M-phenotype clones and that clindamycin may be the drug of choice for the treatment of infections with GAS in penicillin-hypersensitive patients in this area.